Adat Sumando: Tradisi Meminang Masyarakat Pesisir Barus, Tapanuli Tengah - Nur Sehat; Yuni Ratona Tumanggor; Thalita Fadilla (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This article discusses the Sumando Traditional wedding tradition in the coastal communities of Central Tapanuli. This tradition has been carried out by coastal communities for a long time, and is still practiced today. In its history, this tradition originated from the migration of people from Poncan Island to Sibolga, and then spread to other areas around the west coast of Sumatra, including Barus, Tapanuli Tengah. This study combines two methods, namely: field research methods and literature study. Data were obtained from observations in Pananggahan Village and interviews with several traditional leaders and a number of residents. The term sumando comes from the Batak language "suman", which has a similar meaning. Then, the word suman changed to the word sumando which adapted to the accent of the coastal community, but did not change its meaning. This tradition is usually carried out by the coastal communities of Central Tapanuli, especially those who are Muslims. The Sumando Traditional tradition is usually carried out for three days and three nights, both for weddings, circumcisions, and other events, but not at death ceremonies.